An Assessment of Educational leaders’ Multicultural Competences in Ethiopian Public Universities - Geleta, Abeya; Amsale, Frew (European Scientific Journal, ESJ, 2016)
Multicultural Competences of higher education leaders refer directly to the multicultural knowledge, attitudes and skills of the leaders which is the focus of the present study. The demographic changes and the subsequent diversity in Ethiopian HEIs strongly demands the HEIs to be multiculturally competent, their leaders should in turn have the necessary multicultural competencies. In line with this, the multicultural competences of the educational leaders of Ethiopian public universities were investigated. The mixed-methods research approach was used in the study, including semistructured interviews and questionnaires. Academic and administrative officials, office workers and teachers were included in the study as sources of data. Multi-stage, simple random and purposive sampling techniques were employed to select 316 participants for the study. Inferential statistics including mean, standard division, t-tests and one-way ANOVA were used to analyze the quantitative data. The university leaders, academic and administrative staff did not have a considered perspective on pluralism. In addition, there were limited spaces and opportunities for the staff to develop skills and experience in the management of difference as an important aspect of their work and with their interaction with other members of the university community. The staff associations were weak and poorly equipped to provide or promote opportunities for skills development in the management of diversity. Lecturers did not generally receive any preparation on managing within a multicultural setting. The findings confirm the position that the need to prepare university leaders with multicultural knowledge, skills, and dispositions. It is imperative that university leadership adopt multicultural competence as an essential competency within their profession, continue to seek out opportunities to further enhance personal multicultural competence, and infuse it into their daily practices.